2010
DOI: 10.1021/ja1058982
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Purification of Multifunctional Polymer Nanoparticles

Abstract: We report that multi functional polymer nanoparticles approximately the size of a large protein can be "purified", on the basis of peptide affinity just as antibodies, using an affinity chromatography strategy. The selection process takes advantage of the thermo-responsiveness of the nanoparticles allowing "catch and release" of the target peptide by adjusting the temperature. Purified particles show much stronger affinity (Kd app ≈ nM) and a narrower affinity distribution than the average of particles before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 27 publications
1
113
0
1
Order By: Relevance
“…The capture of such toxins would likely require positively charged hydrophobic NPs, a combination that would challenge the immune system. Incorporation of "custom" monomers, designed to bind to specific amino acid or peptide sequences by hydrogen bonding and/or van der Waals interactions, (9), and by applying molecular imprinting (19,29) and/or affinity purification (20) might offer a more fruitful direction to create a synthetic polymer antidote for such toxins. Surface modification of the hydrophobic particles by hydrophilic polymers such as polyethylene glycol would also help to improve biocompatibility and enhance stability of NPs in plasma, although, the modification might also prevent target toxins to be captured by NPs due to steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capture of such toxins would likely require positively charged hydrophobic NPs, a combination that would challenge the immune system. Incorporation of "custom" monomers, designed to bind to specific amino acid or peptide sequences by hydrogen bonding and/or van der Waals interactions, (9), and by applying molecular imprinting (19,29) and/or affinity purification (20) might offer a more fruitful direction to create a synthetic polymer antidote for such toxins. Surface modification of the hydrophobic particles by hydrophilic polymers such as polyethylene glycol would also help to improve biocompatibility and enhance stability of NPs in plasma, although, the modification might also prevent target toxins to be captured by NPs due to steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combined affinity and specificity of the NPs were not sufficient to detoxify melittin in animal models. Recently, we demonstrated that by applying a molecular imprinting (19) or an affinity purification process (20) together with the combination of functional monomers, NPs with greater affinity to the target peptide was achieved. Furthermore, the NPs with enhanced binding affinity showed neutralization of the toxin in vivo (3).…”
mentioning
confidence: 99%
“…Isolated NPs containing a greater proportion of high affinity recognition sites may be more effective in future therapeutic applications. Shea et al reported that multifunctional polymer NPs, approximately the size of a large protein complex (30-50 nm), can be "purified" on the basis of toxic peptide affinity just as antibodies, using an affinity chromatography strategy [22]. In the general protocol for affinity purification of proteins, isolated proteins on the solid affinity support are released by selective elution induced by either pH and/or salt gradients or by adding an excess of competing ligand.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dansyl methacrylamide was synthesized using the method reported. 22 When the NPs were polymerized with greater than 0.1 mol% of dansyl methacrylamide, a mono-modal size distribution of NPs was not obtained because of the tendency of the NPs to aggregate during the preparation process. When the NPs were polymerized with 0.01 mol% of dansyl methacrylamide, NPs with a mono-modal size distribution were obtained.…”
Section: Preparation Of Npsmentioning
confidence: 99%
“…Target affinity can be enhanced by optimizing the feed ratio of functional monomers, 19 by molecular imprinting polymerization 20,21 and/or by affinity purification procedures. 22 It has also been reported that porous membranes polymerized with functional monomers containing carbohydrates can be used as affinity separation media for lectins. [23][24][25] Solid supports for affinity purification media must be carefully designed to achieve an efficient purification process.…”
Section: Introductionmentioning
confidence: 99%